GLUCOSE LEVELS OF PLEURAL EFFUSION FLUID AND HER2 STATUS IN PLEURAL-METASTATIC BREAST CANCER - Muhammad Dhanny Irawan; Desak Gede Agung Suprabawati; Heru Purwanto (Majalah Biomorfologi, 2023)
Highlights Patients with breast cancer who have distant metastases are frequently impacted by pleural effusion. HER2 status was found to be substantially correlated with glucose levels in pleural effusion fluid. Abstract Background: Patients diagnosed with breast cancer who have also been affected by distant metastases often suffer from pleural effusion. The prognosis of malignant pleural effusions worsens when glucose levels in the pleural fluid are low. Elevated levels of anaerobic glycolysis due to HER2 overexpression cause breast cancer cells to take in more glucose. Objective: This study aimed to identify any correlation between glucose levels in pleural fluid and HER2 status in breast cancer patients. Material and Method: In this research, 35 female patients with thoracocentesis pleural metastatic breast cancer participated in an analytical observational study using a cross-sectional design. Patients who had undergone thoracocentesis had their HER2 status determined based on the information included in their medical records in the Integrated Oncology Clinic (Poli Onkologi Satu Atap (POSA)) Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. After obtaining data on glucose levels in pleural fluid and HER2 status, statistical analysis was carried out to determine the relationship between the two parameters. Results: The statistical test results with a 95% significance level obtained p=0.004 (p<0.05), so it could be statistically said that there was a significant relationship between the glucose level of pleural fluid effusion with HER2 status. The obtained OR values were 10.93 and CI=95% (1.87-63.97), so that it could be interpreted that the low-glucose levels of pleural effusion fluid increase the proportion of patients with positive HER2 compared to not low-glucose levels of pleural effusion fluid. The correlation between the glucose level of pleural effusion fluid and HER2 status was moderately positive (Chi-Square Contingency Coefficient = 0.44). Conclusion: Glucose levels in pleural effusion fluid were significantly correlated with HER2 status.